A Note on Differential Net Migration and the Quality of Life - Larson, David A.; Wilford, Walton T. (The Review of Economics and Statistics, 1980)
Professor Liu in Review (1975) presents a social indicators approach to constructing a quality of life (QOL) index. Liu used his composite index to explain differential net migration rates. The explanatory variable the QOL is comprised of nine individual categories: The Economic Status (ES) variable includes among other measures the traditional income per capita and employment components. However Liu surprisingly finds that the ES category is of secondary importance in the to relocate (1975 p. 333). Liu concludes that this finding is slightly different from most all migration studies cited previously which argue that economic motivation dominates all other considerations in making a relocation decision (p. 335). We believe however that Lius findings must be qualified due to the amount of inter- correlation present among his nine QOL input categories. Further we contend that input correlation precludes use of the social indicators approach to determine the importance of economic motivation in the relocation decision. The correlation matrix for Lius nine input variables indicates that the components of his QOL index are highly correlated. As a result it is appropriate to dis- aggregate the QOL index with respect to the ES variable particularly since Lius novel conclusion is that economic motivation as measured by ES is relatively unimportant in explaining net interstate migration – especially nonwhite migration. (excerpt)